Students are humans too: Psychosocial vulnerability of first-year students at the University of Johannesburg - van Breda, A.D. (South African Journal of Higher Education, 2017)
This paper aims to describe the life challenges university students experienced in their first year of study during the transition into academia, how these impacted on their studies at the time, and how these have impacted on their life satisfaction and academic progress over the next year or two. Data were collected using a quantitative survey instrument from 463 second and third year students at the University of Johannesburg, South Africa. Results showed that prevalent and severe life challenges during the first year of study were the death of loved ones and poverty. Most of the life challenges impacted negatively on academic progress and well-being a year or two later, and in combination the pileup of vulnerability in first year has a sustained negative impact on student’s academic progress year a year or two later. Universities need to engage with the whole student as human within their social environment, with both academic and personal development needs.